2007
DOI: 10.1001/archderm.143.5.586
|View full text |Cite
|
Sign up to set email alerts
|

Bath PUVA and Saltwater Baths Followed by UV-B Phototherapy as Treatments for Psoriasis

Abstract: To evaluate the efficacy of psoralens dissolved in a warm-water bath followed by exposure to UV-A irradiation (bath PUVA) or saltwater phototherapy (SW UV-B) compared with tap-water phototherapy (TW UV-B) or UV-B irradiation alone in psoriasis.Design: Multisite, prospective, randomized, controlled trial with 4 parallel groups.Setting: Total of 102 dermatologic outpatient clinics.Patients: Total of 1241 patients with stable psoriasis vulgaris and a Psoriasis Area and Severity Index score of 7 or greater.Interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 36 publications
1
36
0
2
Order By: Relevance
“…Indeed, the aforementioned observations contrast with previous studies showing rather increased UVB-induced erythema reactions after tap water and low-concentration salt water immersions [10,13,14,15]. On the other hand, neither Schiener et al [7] nor Dawe et al [5] observed in their large clinical psoriasis trials an increase in erythemal response to UVB after salt water exposure of different concentrations. Similar results were also reported by Léauté-Labrèze et al [6], who performed the first randomized controlled large-scale trial on BPT.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Indeed, the aforementioned observations contrast with previous studies showing rather increased UVB-induced erythema reactions after tap water and low-concentration salt water immersions [10,13,14,15]. On the other hand, neither Schiener et al [7] nor Dawe et al [5] observed in their large clinical psoriasis trials an increase in erythemal response to UVB after salt water exposure of different concentrations. Similar results were also reported by Léauté-Labrèze et al [6], who performed the first randomized controlled large-scale trial on BPT.…”
Section: Discussionmentioning
confidence: 61%
“…Researchers from Germany have recently performed excellent randomized controlled trials demonstrating that BPT is superior to monophototherapy of psoriasis. The first study, involving 1,241 patients, convincingly demonstrated that bathing in salt water before UVB exposure is superior to UVB monotherapy as well as to tap water baths before UVB exposure [7]. The results of the second trial, involving 143 patients, indicated that BPT using low-concentration saline spa water baths followed by conventional UVB phototherapy was superior to conventional UVB monophototherapy at the end of a 6-week treatment course [8].…”
Section: Introductionmentioning
confidence: 99%
“…Balneo phototherapy Brockow et al [182,183] (EG B) reported an increased PASI 75 response rate to [204]. On the whole, there is an additive benefit of combining a mineral salt water bath with phototherapy (EL 2).…”
Section: Uvb 308 Nm (Excimer Laser)mentioning
confidence: 99%
“…Der gemeinsame Bundesausschuss konnte in der "Dokumentation zum Beratungsverfahren für die Balneophototherapie" keine Überle-genheit der asynchronen gegenüber der synchronen feststellen [16]. Die Behandlungsrichtlinie für die künstliche Photosoletherapie orientiert sich an der Studie des BvDD [24], die zur Aufnahme in den gesetzlichen Gegenstandskatalog geführt hat. Die Behandlungen finden 4-mal wö-chentlich statt, wobei synthetische Salzlö-sungen mit 20-25% zum Einsatz kommen.…”
Section: Künstliche Photosoletherapie (Kpst)unclassified